The Responsibility Of Holding Company Towards Bankruptted Subsidiaries Based On Law No. 40 Of 2007 About Limited Companies - Aryaputra Singgih , Jay; Azhar Siregar, Hamdan (International Journal of Educational Research & Social Sciences, 2023)
The purpose of this research is to identify and analyze the juridical liability of the holding company to its bankrupt subsidiary and the holding company's responsibility to its bankrupt subsidiary. The research method used in this research is normative qualitative. The holding company's juridical responsibility for a bankrupt subsidiary, in certain circumstances the holding company can be held accountable for its subsidiary based on the Piercing The Corporate Veil principle. The application of this principle to holding companies can occur either through legal agreements or based on certain agreements. Implementation of holding company responsibilities for bankrupt subsidiaries in the case of PT. Ometraco Corporation, Tbk. dar. PT. Ometraco Multi Artha pointed out that the Supreme Court is of the opinion that PT. Ometraco Corporation, Tbk. as the holding company is also responsible for the debt of PT. Ometraco Multi Artha as a bankrupt subsidiary based on an agreement.